PharmGKB, an Integrated Resource of Pharmacogenomic Knowledge. Issue 8 (13th August 2021) - Gong, Li; Whirl‐Carrillo, Michelle; Klein, Teri E.
Abstract: The Pharmacogenomics Knowledgebase (PharmGKB) is an integrated online knowledge resource for the understanding of how genetic variation contributes to variation in drug response. Our focus includes not only pharmacogenomic information useful for clinical implementation (e.g., drug dosing guidelines and annotated drug labels), but also information to catalyze scientific research and drug discovery (e.g., variant‐drug annotations and drug‐centered pathways). As of April 2021, the annotated content of PharmGKB spans 715 drugs, 1761 genes, 227 diseases, 165 clinical guidelines, and 784 drug labels. We have manually curated data from more than 9000 published papers to generate the content of PharmGKB. Recently, we have also implemented an automated natural language processing (NLP) tool to broaden our coverage of the pharmacogenomic literature. This article contains a basic protocol describing how to navigate the PharmGKB website to retrieve information on how genes and genetic variations affect drug efficacy and toxicity. It also includes a protocol on how to use PharmGKB to facilitate interpretation of findings for a pharmacogenomic variant genotype or metabolizer phenotype. PharmGKB is freely available at http://www.pharmgkb.org . © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Navigating the homepage of PharmGKB and searching by drug Basic Protocol 2 : Using PharmGKB to facilitate interpretation of pharmacogenomic variant genotypes or metabolizer phenotypes